OPINI KHALAYAK PADA COCAST MENTAL HEALTH EPISODE 9 TERHADAP PERUBAHAN PERILAKU GEN Z DI KOMISI KEPEMUDAAN KEUSKUPAN AGUNG MEDAN - Saurma MGP Siahaan; Salman Hasibuan; Rachel Mia Lorenza Lbn. Toruan; Yasinta Vika Laia (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to examine audience opinions regarding the "Cocast Mental Health" program (Episode 9) and its impact on behavioral changes among Generation Z members of the Youth Commission of the Archdiocese of Medan. The study employs behavioral change theory and the concept of audience opinion, utilizing a qualitative approach. Data was collected through in-depth interviews with Youth Commission members who had watched the episode. A thematic analysis was conducted to identify emerging patterns of opinion and behavioral changes. The results indicate that the "Cocast Mental Health" episode had a positive impact by enhancing Gen Z's understanding of and awareness regarding mental health. Predominant audience opinions were positive, particularly regarding the communicative and relevant presentation of the material; this fostered behavioral changes such as increased openness in discussing mental health, improved stress management, and active participation in activities supporting psychological well-being. Furthermore, a reduction in negative perceptions regarding mental health issues was observed among Gen Z, reflected in more empathetic and supportive attitudes. This study underscores the importance of digital educational media—such as "Cocast Mental Health"—as an effective instrument for shaping constructive public opinion and fostering positive behavioral changes among the younger generation. Keywords: Public Opinion; Mental Health; Gen Z Behavior   Abstrak: Penelitian ini bertujuan untuk mengetahui opini khalayak pada episode 9 program Cocast Mental Health terhadap perubahan perilaku Generasi Z di Komisi Kepemudaan Keuskupan Agung Medan. Penelitian ini menggunakan Teori perubahan perilaku dan konsep Opini Khalayak dengan pendekatan kualitatif. Data dikumpulkan melalui wawancara mendalam dengan anggota Komisi Kepemudaan yang telah mengikuti episode tersebut. Analisis data dilakukan secara tematik untuk mengidentifikasi pola opini dan perubahan perilaku yang muncul. Hasil penelitian menunjukkan bahwa episode Cocast Mental Health memberikan dampak positif dalam meningkatkan pemahaman dan kesadaran Gen Z terhadap kesehatan mental. Opini khalayak yang dominan bersifat positif terhadap penyajian materi yang komunikatif dan relevan, sehingga mendorong perubahan perilaku berupa peningkatan keterbukaan dalam berdiskusi tentang kesehatan mental, pengelolaan stres yang lebih baik, serta partisipasi aktif dalam kegiatan yang mendukung kesejahteraan psikologis. Selain itu, ditemukan adanya penurunan pandangan negatif terhadap masalah mental di kalangan Gen Z yang tercermin dari sikap lebih empatik dan suportif. Penelitian ini menegaskan pentingnya media edukasi digital seperti Cocast Mental Health sebagai instrumen efektif dalam membentuk opini publik yang konstruktif dan mendorong perubahan perilaku positif di kalangan generasi muda. Kata kunci: Opini Khalayak; Mental Health; Perilaku Gen Z